The impact of board structure of corporate governance on credit risk: special reference to the banks listed in Colombo Stock Exchange in Sri Lanka - Sameera, T.K.G. (Faculty of Management Studies & Commerce, University of Jaffna, 2018)
The recent financial crisis and corporate failures at the beginning of the millennium, the emphasis of the business community in corporate governance has shifted towards internal control and risk management issues. As a result, discussion on the impact of corporate governance practices on risk has reached an unprecedented level for academics and practitioners. The rising Non-Performing loans is a threat to any bank since it exposes the bank to many risks. Credit risk is the potential threat to a bank due to a borrower or a counterparty failing to meet its obligations in accordance with the agreed terms. It would expose a bank to many other related risks such as liquidity risk and solvency risk. Accordingly, prudent management of credit risk would ensure the long-term solvency of a bank. Credit risk remained the main risk area of concern to the Sri Lankan banks owing to higher share of loans and advances in the total assets portfolio. Therefore, the purpose of this study is to investigate the impact of board structure on credit risk of banks listed in Colombo Stock Exchange in Sri Lanka. The study was based on the secondary data. Thirteen companies were selected from the listed companies in Colombo Stock Exchange during the period of 2013 to 2017. The Board Size, Board Independence and Meeting Frequency were considered as independent variables, whereas, credit risk as dependent variable. The credit risk was proxied by Non-Performing Loan ratio. The control variables were Financial Leverage and Firm Size. A regression model was used to establish the relationship between board structure and credit risk. The overall results and findings statistically confirmed that the board size and board independence have significantly and negatively impact over the credit risk. Board meeting frequency, firm size and financial leverage have no significant impact on credit risk. Hence, the evidence suggests that the bank increases its board size and majority representation of independent non executive directors in the board are important factors as they help the reduce the credit risk expose by the banks.. The participation of independent non-executive members in large proportion improves the independence of the board and increases the capacity of corporate boards to effectively advise, monitor and consequently, reduces the credit risk.
Keywords: corporate governance; credit risk; Non-Performing Loan